1993
DOI: 10.1111/j.1533-8525.1993.tb00110.x
|View full text |Cite
|
Sign up to set email alerts
|

Dilemmas of Femininity: Gender and the Social Construction of Sexual Imagery

Abstract: This work builds on an interactive, interpretive approach to the study of cultural texts in an investigation of how images of gender and sexuality in music television (MTV) are read by the audience. After viewing a music video by Michael Jackson, 80 respondents described the video's portrayal of feminine and masculine images. A content analysis of the respondents' open-ended descriptions of the images indicate that there are significant gender differences in how young women and men socially construct the mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…Viewers typically report watching between half-an-hour and 2 hr of these programs per day (Sun & Lull, 1986). Content analyses of music videos have shown that, like other forms of popular culture, the portrayal of women is decidedly sexist in orientation with high levels of sex-role stereotyping (Kalof, 1993). In particular, the physical appearance of women is emphasized (Gow, 1996) and they are commonly depicted as thin and attractive, usually provocatively or scantily clad, and often involved in implicitly sexual or subservient behavior (SommersFlanagan, Sommers-Flanagan, & Davis, 1993;Vincent, Davis, & Boruszkowski, 1987).…”
Section: Introductionmentioning
confidence: 98%
“…Viewers typically report watching between half-an-hour and 2 hr of these programs per day (Sun & Lull, 1986). Content analyses of music videos have shown that, like other forms of popular culture, the portrayal of women is decidedly sexist in orientation with high levels of sex-role stereotyping (Kalof, 1993). In particular, the physical appearance of women is emphasized (Gow, 1996) and they are commonly depicted as thin and attractive, usually provocatively or scantily clad, and often involved in implicitly sexual or subservient behavior (SommersFlanagan, Sommers-Flanagan, & Davis, 1993;Vincent, Davis, & Boruszkowski, 1987).…”
Section: Introductionmentioning
confidence: 98%
“…Adolescent consumers continue to watch music videos regularly and remain the target audience for MTV, BET and the like (Kalof 1993;Lewis 1990;"MTV: Music Television Profile and Network Contact Info" 2005;Rideout 2003;Smith and Boyson 2002;Tiggemann and Slater 2003). Past research shows that music video content from the 1980s and 1990s was sexy (Sherman and Dominick 1986;Hansen and Hansen 2000;McKee and Pardun 1996) but that it also typically emphasized sexual innuendo and suggestiveness rather than overt/explicit depictions (Baxter et al 1985;Gow 1990;Sommers-Flanagan et al 1993).…”
Section: Introductionmentioning
confidence: 94%
“…Attentional processes suggest that for a mediated model to have a legitimate chance at gaining the attention of a potential attendee, that model must be salient, striking, conspicuous, and/or prominent (Bandura 2002). MTV and other music video channels are a popular form of entertainment for adolescents (Kalof 1993;Smith and Boyson 2002;Tiggemann and Slater 2003). It is estimated that 3 out of 4 young adults (16 to 24 years) watch MTV every day (Rideout 2003).…”
Section: Introductionmentioning
confidence: 98%
“…In research on how audiences receive messages encoded in music television texts, both Kalof (1993) and Brown and Schultz (1990) documented gender differences in the interpretation of text meanings. These researchers established that the reading of a text is an interactive, interpretive process.…”
Section: Introductionmentioning
confidence: 97%